2019
DOI: 10.1016/j.paid.2019.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Prejudiced and unaware of it: Evidence for the Dunning-Kruger model in the domains of racism and sexism

Abstract: The version presented here may differ from the published, performed or presented work. Please go to the persistent GRO record above for more information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…Implicit bias is not specific to a particular country. Multiple forms of implicit bias have been reported globally, such as implicit racial bias in Italy, 10 implicit racial and gender bias in UK, 11 and implicit weight bias in Singapore. 12 The form of implicit bias that plays an important role, in intergroup relations in general and in patient care specifically in a given country, is determined largely by its cultural, historical, and economic contexts.…”
mentioning
confidence: 99%
“…Implicit bias is not specific to a particular country. Multiple forms of implicit bias have been reported globally, such as implicit racial bias in Italy, 10 implicit racial and gender bias in UK, 11 and implicit weight bias in Singapore. 12 The form of implicit bias that plays an important role, in intergroup relations in general and in patient care specifically in a given country, is determined largely by its cultural, historical, and economic contexts.…”
mentioning
confidence: 99%
“…White Americans now perceive this balance of discrimination to disfavor Whites, in a finding has been cited in media outlets such as the New York Times (2011) and NPR (2011) and has been frequently cited in social science publications (e.g., Todd, Bodenhausen, & Galinsky, 2012;Mayrl & Saperstein, 2013;Cabrera, 2014;Hughley, 2014;Wilkins, Wellman, Babbitt, Toosi, & Schad, 2015;Major & Kaiser, 2017;and West & Eaton, 2019).…”
Section: Indicated Thatmentioning
confidence: 99%
“…Perceptions of this balance have the potential to influence legal outcomes and influence support for race-targeted programs (Carter and Murphy, 2015, p. 274). Survey results reported in Norton and Sommers (2011) indicated that White Americans now perceive this balance of discrimination to disfavor Whites, in a finding that has been cited in media outlets such as the New York Times (2011) and NPR (2011) and has been frequently cited in social science publications (e.g., Todd et al, 2012;Mayrl and Saperstein, 2013;Cabrera, 2014;Hughey, 2014;Wilkins et al, 2015;Major and Kaiser, 2017;and West and Eaton, 2019).…”
mentioning
confidence: 99%